The Sense of Community of Online Taxi Drivers - Ratri Arista; Acintya Ratna Priwati; Putri Yunifa (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2021)
This study explores how the sense of community (SOC) is represented in online taxi driver communities. This study in Yogyakarta utilized qualitative descriptive research. Data collection was conducted using in-depth interview by snowball sampling method. Thematic analysis is used with theory-driven approach of SOC framework by McMillan and Chavis (1986). Nine male online taxi drivers were the participants. The findings show that all four SOC components are present: membership, influence, integration & need fulfillment, and shared emotional connection. Membership has permeable expanding boundaries with multiple membership and multilayered communities with conventional taxi drivers involvement. Bidirectional influence represents the influence component. Integration and needs fulfillment exists by their informational and helping shared values. Shared emotional connection is represented with the ‘brotherhood’ concept as their main community value. This study contributes to the literature on how sense of community is represented among informal workers amidst the heightened popularity of gig economy.